PENERAPAN STRATEGI PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA KELAS IV SDN 6 KADUR - Sumidah, Sumidah; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted because of the low learning outcomes of IPS students of grade IV SDN 6 Kadur. Of the 22 students, only 8 people (36.36%) achieved the level of mastery of learning materials, in accordance with the Minimum Criterion Score (KKM) applied at the school, which is 70 and above. Thus, IPS learning that has been implemented is said to be unsuccessful, because the classical students are required complete 63.88% and above. To overcome this problem, researchers apply guided inquiry learning strategies. The purpose of this research is to improve the learning result of IPS class IV SDN 6 Kadur. The result of data analysis found that the average score of 61.59 base score increased in cycle I by 14.02% to 70.23. In cycle II the average value also increased by 31.30% to 80.91. In the initial scores of classical completeness of student learning IPS is 36.26%. After applied guided inquiry strategy in cycle I classical completeness of student learning result increased to 68,18% and in cycle II classical completeness of student learning result increased to 86,36%. Increased percentage of teacher activity scores from 58% with enough category increased to 92% in very good category. Furthermore on student activity also happened increase percentage of activity score 54 student with category less become 96% at end of cycle II. Increased student activity is also accompanied by an increase in student learning outcomes from 61.59 with the category less to 80.91 with good category. From the results of the research analysis can be concluded that the implementation of guided inquiry learning strategy can improve the learning outcomes of IPS students of grade IV SDN 6 Kadur.Keywords: guided inquiry learning strategy, IPS learning result